The Ulul Albab Spiritual Leadership Construct and Its Impact on Psychological Well-Being : A CFA Examination among Campus Da'wah Activists - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Milna Sari; Wildan Izzatul Haq (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
This study rigorously investigates the Ulul Albab spiritual leadership construct and its impact on psychological well-being among campus da'wah activists, employing a Confirmatory Factor Analysis (CFA) approach grounded in both theoretical integration and empirical data. The inquiry draws upon a meta-analysis of 47 quantitative studies encompassing a total of 12,847 respondents from leading universities in Indonesia, Malaysia, and Brunei Darussalam, spanning the years 2018 to 2024. This methodological scope enhances the external validity of the findings. The CFA results confirm that the Ulul Albab spiritual leadership model exhibits a robust level of model fit, as indicated by optimal statistical indices (χ²/df = 2.34; CFI = 0.956; TLI = 0.943; RMSEA = 0.047; SRMR = 0.039), suggesting strong coherence between the theoretical construct and field data. The three core dimensions conceptualized in this model are statistically validated through high factor loadings: intellectual spirituality (0.847), Islamic transformational leadership (0.823), and emotional-spiritual intelligence (0.791), each serving as integral pillars of the Ulul Albab paradigm. Furthermore, structural regression analysis reveals a significant effect of Ulul Albab spiritual leadership on the psychological well-being of da'wah activists (β = 0.673; p < 0.001; R² = 0.453), thereby affirming the model's predictive strength in fostering individual potential rooted in Islamic spiritual values. These findings reinforce the theoretical propositions advanced by Garden, M. (2004), Fry (2003), and Zohar and Marshall (2000) regarding the significance of spiritual leadership within organizational dynamics. However, this study offers a novel conceptual contribution through the epistemological synthesis of the Ulul Albab construct, integrating intellectual and spiritual intelligence within a holistic Islamic framework. Unlike Western-based models of spiritual leadership proposed by Fry and Nisiewicz (2020), the Ulul Albab construct demonstrates a notable advantage in the dimension of intellectual spirituality, as evidenced by its higher factor loading (0.847 compared to 0.634), underscoring the imperative of balancing dzikir and fikir as both ethical and cognitive foundations in contemporary Islamic leadership.